A chart of the world on Mercator's projection: shewing the principal ocean steam routes, the submarine telegraphs &c. - Stanford, Edward, 1827-1904 (Edward Stanford, 1887)
Map shows major political divisions, cities, submarine cable lines, and ocean travel routes for North, South, and Central America, Greenland, and western Europe and Africa. Includes relative time zones. Inset: "The Arctic Regions." Relief shown by hachures. Scale not given.